2007
DOI: 10.1093/annonc/mdm170
|View full text |Cite
|
Sign up to set email alerts
|

Akt-induced endocrine therapy resistance is reversed by inhibition of mTOR signaling

Abstract: Our preliminary findings in experiments with RAD-001 indicate that cotreatment with mTOR inhibitors and either Let or ICI reverses the Akt-mediated resistance and restores responsiveness to antiestrogens. Concurrent ER and mTOR inhibition is therefore an effective strategy to overcome growth factor-induced resistance and bears significant implications for optimal clinical development of these agents in breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(98 citation statements)
references
References 19 publications
5
89
0
4
Order By: Relevance
“…Activation of AKT and overexpression of EGF and ERBB receptors are consistent with previous observations in MCF7-LTED cells and related breast cancer conditions (Masamura et al, 1995;Jeng et al, 1998;Shim et al, 2000;McClelland et al, 2001;Knowlden et al, 2003;Osborne et al, 2005;Yue et al, 2005;Song et al, 2006;Beeram et al, 2007;LewisWambi et al, 2008;Santen et al, 2008;Ghayad et al, 2009). Notably, ERBB2 amplification was associated with resistance to endocrine therapies (Ellis et al, 2006), and treatment with the mTOR inhibitor RAD001 increased letrozole efficacy in a neoadjuvant setting of ERa-positive breast cancer (Baselga et al, 2009).…”
Section: Resultssupporting
confidence: 85%
“…Activation of AKT and overexpression of EGF and ERBB receptors are consistent with previous observations in MCF7-LTED cells and related breast cancer conditions (Masamura et al, 1995;Jeng et al, 1998;Shim et al, 2000;McClelland et al, 2001;Knowlden et al, 2003;Osborne et al, 2005;Yue et al, 2005;Song et al, 2006;Beeram et al, 2007;LewisWambi et al, 2008;Santen et al, 2008;Ghayad et al, 2009). Notably, ERBB2 amplification was associated with resistance to endocrine therapies (Ellis et al, 2006), and treatment with the mTOR inhibitor RAD001 increased letrozole efficacy in a neoadjuvant setting of ERa-positive breast cancer (Baselga et al, 2009).…”
Section: Resultssupporting
confidence: 85%
“…A potential mechanism of endocrine resistance is aberrant signaling through the PI3K signaling pathway (17,25). Preclinical studies have shown that breast cancer cells with upregulated AKT signaling are resistant to ET, but sensitivity may be restored by treatment with mTOR inhibitors (26,27). However, no clinical study has demonstrated that secondary resistance to ET is associated with increased PI3K signaling in patients, and synergy between ET and everolimus has not been demonstrated in patient's tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the expression of Ki-67 (proliferation-related Ki-67 antigen), phospho-S6 (phosphorylated S6 ribosomal protein), cyclin D1, and progesterone receptor signatures in breast cancer tissues were shown to be useful pharmacodynamic biomarkers that associated with fewer events in estrogen receptor-positive patients by combining everolimus with letrozole as compared to everolimus alone (56). These results suggested that the PI3K/Akt/mTOR pathway plays a key role in patients' response to anti-endocrine therapy (56)(57)(58). These examples demonstrate potential applications of using gene transcript signatures to support our molecular level understanding and prediction of clinical responses.…”
Section: Transition To Early Clinical Developmentmentioning
confidence: 99%